2013
DOI: 10.12732/ijam.v26i5.5
|View full text |Cite
|
Sign up to set email alerts
|

\mathversion{bold}SPECTRAL CONTINUITY OF $(p,k)$-QUASIPOSINORMAL OPERATOR AND $(p,k)$-QUASIHYPONORMAL OPERATOR

Abstract: An operator T ∈ B(H) is said to be (p, k)-quasiposinormal operator, if T * k (c 2 (T * T ) p − (T T * ) p )T k ≥ 0 for a positive integer 0 < p ≤ 1, some c > 0 and a positive integer k. In this paper, we prove that, the (p, k) quasi-posinormal operator is a pole of resolvent of T * . Then we prove that if {T n } is a sequence of operators in the class (p, k) − Q and (p, k) − QP which converges in the operator norm topology to an operator T in the same class, then the functions spectrum, Weyl spectrum, Browder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…[80] Piperazine sulfonamide derivatives of isoxazolines and isoxazoles, as 5-HT 2A/C receptor antagonists, have been described as antidepressants. [81] Antidepressanta ctivity has also been noted by 3,4,5-trisubstituted isoxazolines 11 (Figure 4) incorporating alicycles (e.g.,p iperazines), carboaromatics (e.g.,p henyls) and heteroaromatics (e.g.,thiophenes). [82] The cholinergic system has long been linked to cognitive processes.T he modulation of muscarinic and nicotinic acetylcholine receptors( mAChRs and nAChRs, 12;F igure 5), present in the brain, exerts ap rofounde ffect on depression and anxi- Reviews ety.Nootropics, also known as cognition enhancers, have accordingly been developed (13 and 14; Figure 5).…”
Section: Psychoactive Drugs (Psychotropics)mentioning
confidence: 96%
“…[80] Piperazine sulfonamide derivatives of isoxazolines and isoxazoles, as 5-HT 2A/C receptor antagonists, have been described as antidepressants. [81] Antidepressanta ctivity has also been noted by 3,4,5-trisubstituted isoxazolines 11 (Figure 4) incorporating alicycles (e.g.,p iperazines), carboaromatics (e.g.,p henyls) and heteroaromatics (e.g.,thiophenes). [82] The cholinergic system has long been linked to cognitive processes.T he modulation of muscarinic and nicotinic acetylcholine receptors( mAChRs and nAChRs, 12;F igure 5), present in the brain, exerts ap rofounde ffect on depression and anxi- Reviews ety.Nootropics, also known as cognition enhancers, have accordingly been developed (13 and 14; Figure 5).…”
Section: Psychoactive Drugs (Psychotropics)mentioning
confidence: 96%
“…17 For decades, there is considerable interest in introducing fluorine-containing groups into organic molecules since the growing application of organic fluorine compounds in pharmaceuticals. 20 The synthesis of key intermediates 9 is depicted in Scheme 2. β-ethyloxyvinyl fluoroalkyl ketones 5 were prepared from ethyl vinyl ether and its derivatives with fluoroalkylacetic anhydride under base condition. 19 However, literature survey showed that the incorporation of these fluoroalkyl groups into oxazolidinones has not been studies systematically.…”
Section: Introductionmentioning
confidence: 99%
“…These interesting biological activities have stimulated the search for efficient procedures with wide generality for building this ring system. [3][4][5][6] Levulinic acid (LA) is a well-known biogenic product from plant biomass. LA can be produced from D-glycopyranose of starch and cellulosic feedstocks.…”
Section: Introductionmentioning
confidence: 99%